Effects of the quality and quantity of sleep hours in patients with arterial hypertension: A narrative review - Cabrera-Guzmán, Juan Carlos (2021)
Background: High prevalence of arterial hypertension (HTN) is a global public health problem. Various conditions compromise an adequate control of this disease, being one of recent interest the sleep disturbances. We describe through a narrative review the recent findings in the literature about the effects of the quality and quantity of sleep on hypertensive patients. Eighteen articles that met the inclusion criteria were selected for this review. This review will detail the findings related to complications linked to the duration and quality of sleep in patients with HTN, as well as predictive factors of poor sleep quality in these patients.